Liquid Organic Frameworks: A Liquid Crystalline 8‐Connected Network with Body‐Centered Cubic Symmetry. Issue 47 (7th September 2020) - Chen, Changlong; Poppe, Marco; Poppe, Silvio; Tschierske, Carsten; Liu, Feng
Abstract: Liquid state self‐assembly is important for the understanding of the complex structures developed in abiogenesis and biogenesis as well as for numerous potential technological applications. Herein we report the first body‐centered cubic liquid crystalline phase with 8‐connected network topology and open octahedral network structure. It is formed by dynamic soft self‐assembly of X‐shaped polyphiles with oligo( para ‐phenylene‐ethynylene) cores. The π‐conjugated rods with perfluorinated inner benzene rings form networks conjoined by eight‐way junctions, which are formed by nano‐segregated spheres involving hydrogen‐bonded polar end groups, while the branched aliphatic chains at opposite sides of the cores fill the continuum. This novel cubic phase is based on the I‐WP minimal surface separating the frameworks of polyaromatic cores from the most disordered chain segments. It can also be considered as a dense sphere packing. Such liquid organic frameworks, representing hybrids of sphere packings and networks could be of interest for organic photonics and other technologies. Abstract : The first 8‐connected network based on the I‐WP minimal surface is formed by dynamic soft self‐assembly of X‐shaped polyphiles with oligo( para ‐phenylene‐ethynylene) cores. This Im 3 ‾ m cubic liquid‐crystalline phase is one of a new kind of cubic phases combining a network structure of rod‐bundles interconnected by polar spheres.